The Influence of AIS, TQM, and Internal Control on the Performance of F&B Franchises in Bengkulu City - Prayoga, Imam Hazazi; Martiah, Lisa (Penerbit Goodwood, 2025)
Purpose: With the increasing franchise performance, it is expected to open more job opportunities, increase regional income, and contribute to local economic growth. Methodology/approach: This study used an associative method with a quantitative approach. The sample used was 37 respondents. Data collection was carried out by distributing questionnaires, tested and analyzed using SPSS software. Data analysis was carried out using the multiple linear regression method. Results/findings: Based on research findings, the three variables, namely Accounting Information Systems, Total Quality Management (TQM), and Internal Control, have been proven to have a significant influence on improving the performance of F&B franchises in Bengkulu City. Conclusions: This study shows that Accounting Information Systems, Total Quality Management (TQM), and Internal Control have a positive and significant impact on the performance of F&B franchises in Bengkulu City. Accounting Information Systems have the strongest influence with a significance value of 0.001, followed by TQM with a significance value of 0.019, and Internal Control with a significance value of 0.048. Limitations: The scope of the research is limited, the focus of the research only covers the food and beverage sector, this research uses a cross-sectional design, namely it is carried out at a certain time, so it cannot describe the dynamics or changes in variables over time. Contribution: The contribution of this research lies in strengthening empirical evidence the importance of integration between information systems, quality management, and internal control in improving organizational performance, especially in the F&B franchise sector and for business actors and franchise managers in developing more effective and data-based internal management strategies.